OPTIMALISASI PEMBELAJARAN IPA MELALUI METODE DEMONSTRASI: PEMAHAMAN KONSEP PERUBAHAN WUJUD BENDA PADA SISWA KELAS III - Sari, Novita; Astuti, Lina Sisni (Journal of Professional Elementary Education, 2025)
The results of the observation showed that the low learning outcomes of students were related to the lack of interactive learning process and low learning motivation. Teachers play an important role in improving collaborative learning, so it is necessary to choose teaching strategies and techniques that are in accordance with the characteristics of students. One approach used is the resonance method, which aims to improve the learning outcomes of grade III students of Sidanegara 09 Cilacap Elementary School on the material of changes in the shape of objects. This observation was carried out through Classroom Action Research (CAR) for two cycles, with 35 students as subjects. Each cycle includes the stages of planning, implementation, observation, and reflection. The pre-cycle results showed that only 12 students (34.28%) had completed learning. After the action in cycle I, the number of students who completed increased to 26 students (74.28%), and in cycle II to 32 students (91.42%). Only 3 students had not achieved completion. There was an increase of 17.14% between cycles I and II. These results prove that the success indicator has been achieved. Thus, this method has proven effective in improving student learning outcomes on changes in the material of the shape of objects in the surrounding environment.